High HIV prevalence and incidence among women in Southern Mozambique: Evidence from the MDP microbicide feasibility study. - Sibone Mocumbi; Mitzy Gafos; Khatia Munguambe; Ruth Goodall; Sheena McCormack; Microbicides Development Programme (PLoS ONE)
Background The study aimed to assess the feasibility of conducting large scale HIV prevention clinical trials in Mozambique by measuring HIV prevalence and incidence among women of reproductive age. This paper describes the baseline socio-demographic characteristics of the Mozambique Microbicides Development Programme (MDP) feasibility cohort, baseline prevalence of HIV and other STIs, and HIV incidence. Methods The Mozambique MDP feasibility study was conducted from September 2007 to August 2009 in urban Mavalane and rural Manhiça, in Southern Mozambique. Sexually active, HIV negative women aged 18 years and above were recruited to attend the study clinic every 4 weeks for a total of 40 weeks. At baseline, we collected demographic and sexual behaviour data, samples to test for sexually transmitted infections (STI) and conducted HIV rapid testing. STI and HIV testing were repeated at clinical follow-up visits. We describe HIV prevalence of women at screening, the demographic, behavioural and clinical characteristics of women at enrolment, and HIV incidence during follow-up. Results We screened 793 women (369 at Mavalane and 424 at Manhiça) and enrolled 505 eligible women (254 at Mavalane and 251 at Manhiça). Overall HIV prevalence at screening was 17%; 10% at Mavalane and 22% at Manhiça. Women screened at Manhiça were twice as likely as women screened at Mavalane to be HIV positive and HIV positive status was associated with younger age (18-34), lower educational level, not using a reliable method of contraception and being Zionist compared to other Christian religions. At enrolment contraceptive use was low in both clinics at 19% in Mavalane and 21% in Manhiça, as was reported condom use at last sex act at 48% in Mavalane and 25% in Manhiça. At enrolment, 8% of women tested positive for Trichomonas vaginalis, 2% for Neisseria gonorrhoeae, 4% for Chlamydia trachomatis and 46% for bacterial vaginosis. In Manhiça, 8% of women had active syphilis at screening. HIV incidence was 4.3 per 100 person years at Mavalane and 9.2 per 100 person years at Manhiça. Conclusions We demonstrated the ability to recruit a cohort of women at risk of HIV who were willing to participate in clinical research. The high HIV incidence necessitates additional action around HIV prevention for women and offers opportunities to evaluate the impact of available prevention options, such as treatment as prevention and oral PrEP. The high HIV incidence and STI prevalence also offers opportunities to evaluate the added benefit of potential prevention options such as new formulations of oral PrEP, vaginal microbicides (also called topical PrEP), vaccines, and multi-purpose technologies for HIV, STIs and contraception.